Acute effect of dynamic stretching versus combined static dynamic stretching on speed performance among male Sukma Sarawak 2016 sprinters - Syahir Brahim (Tanjong Malim, 2020)
Acute effect of dynamic stretching versus combined static dynamic stretching on speed performance among male Sukma Sarawak 2016 sprinters by Syahir Brahim